Evaluation of different species of Cymbidium under high hills of Uttarakhand - TIWARI, A K; YADAV, L B; TIWARI, ARCHANA; GAUR, A P (The Indian Journal of Agricultural Sciences, 2011)
Eleven Cymbidium species were evaluated for morphological and floral characters in the high hills situation of Uttarakhand. Among the tested species, the survival rate were maximum in C. hookerianum, C.longifolium and C.gigantium. Due to heavy infestation of Fusarium oxysporum and Alternaria alternata, C.tigrinum and C.lancifolium were almost eliminated from population at the end of third year. Flowering did not occur in C.devonianum and C.eburneum. Based on an overall evaluation, C.elegans,C.hookerianum C.gigantium and C. mastersii were identified as the most promising genetic material that could be used in breeding for evolving desirable hybrids and for their commercial cultivation in high hills of Himalayas in Uttarakhand.